Establishment of trauma treatment teams within a regional severe trauma treatment system in China: study protocol for a national cluster-randomised trial. Issue 12 (4th December 2018) - Wang, Yu; Liu, Hui-Xin; Wang, Yan-Hua; Zhang, Ya-Jun; Zhang, Jin-Jun; Huang, Wei; Jiang, Bao-Guo; Wang, Tian-Bing
Abstract : Introduction: The implementation of first aid processes for patients with trauma in China faces significant challenges. These challenges include long response times of prehospital first aid services, lack of information exchange between prehospital first aid services and in-hospital emergency services, lack of a professional rescue team in the majority of hospitals, and lack of standardised training for prehospital and in-hospital emergency personnel. The purpose of the trial is to guide the establishment of an urban trauma treatment system in China, highlight the construction of a trauma treatment system tailored to the Chinese context and improve levels of medical treatment by selecting approximately 100 counties across China as pilots to establish a regional trauma treatment system. Methods and analysis: A cluster-randomised controlled trial will be performed in 98 county-level research institutes. Included research institutes will be randomised into an experimental group and a control group. Patients in both experimental and control groups will receive basic treatments. A trauma treatment team will be established in the experimental group. The primary outcome measure is in-hospital mortality rate of patients. The secondary outcome measures include mortality rate of patients within 30 days after trauma attack and within 30 days after discharge, the time between arrival in the institution and receiving consultation, and the time from admission to the start of surgery. The effects of establishment of trauma treatment teams on the treatment of severe trauma will be evaluated in all counties. Ethics and dissemination: The procedures have been approved by The Medical Ethics Committee of Peking University People's Hospital (No.2017PHB098-01) and conform to the Declaration of Helsinki. Data will be collected and analysed in accordance with participant privacy laws and regulations. Results will be disseminated through policy briefs, workshops, peer-reviewed publications and conferences. Trial registration number: NCT03363880 ; Pre-results.